Occurrence of tinnitus and peripheral sensory neuropathy in women during chemotherapy treatment of breast cancer - Simone Yuriko Kameo; Ricardo Barbosa-Lima; Josilene Luciene Andrade; Bruno Ferreira Amorim; Glebson Moura Silva; Pabliane Matias Lordelo Marinho; Namie Okino Sawada (Hospital de Clínicas de Itajubá, 2021)
Objective: To analyze the occurrence of tinnitus and peripheral sensory neuropathy in women during breast cancer chemotherapy. Methods: This is a retrospective analytical study with a quantitative approach, performed in medical records of an oncology outpatient service between February 2014 and February 2015, using the toxicities scores of Common Terminology Criteria for Adverse Events (CTCAE). Results: Considering 181 patients with breast cancer who met the inclusion criteria, 49.2% reported tinnitus at some point of the treatment, while 65.1% peripheral sensory neuropathy. In both conditions, the predominant severity score was grade 1, with frequencies of 23.8% and 33.1%, respectively. A significant, positive and weak correlation was observed between the severity of tinnitus and peripheral sensory neuropathy (ρ = 0.325 and p = 0.001), as well as very weak between the number of complete cycles of chemotherapy and tinnitus (ρ = 0.195 and p = 0.009) and neuropathy peripheral sensory (ρ = 0.237 and p = 0.002). Conclusions: Tinnitus and peripheral sensory neuropathy were frequent toxicities during chemotherapy treatment of breast cancer, and both manifested with low severity/functional impact in most participants.